IMMOBILIZATION OF PAPAIN ON CHITOSAN - Sari Edi Cahyaningrum; Narsito Narsito; Sri Juari Santoso; Rudiana Agustini (Universitas Gadjah Mada, 2008)
In this study, papain was immobilized on chitosan with Mg(II) cosslinked agent. Studies on free and immobilized papain systems for determination of optimum pH, optimum temperatur, thermal stability and reusability were carried out. The results showed that free papain had optimum pH 6.5 and optimum temperature 55 °C while the immobile papain hadoptimum pH 8 and optimum temperature 80 °C. The thermal stability of the immobilized papain, relative to that of the free papain, was markedly increased. The immobilized papain can be reused for at least six times.